Characterization of chitin and chitosan extracted from shrimp shells by two methods (2010)
ABSTRACT:Shrimp shells from Penaeus Vannamei species were hydrolyzed for chitin extraction by a chemical and a papain enzymatic method. Composition of shells was analyzed and their microstructure was characterized before and after hydrolysis by microscopy. Chitin fibers arrangement in the tissue was preserved after chemical extraction, but after papain hydrolysis the tissue presented structural disarrangement indicating that papain reacts indistinctly with peptidic and N-acetyl linkages. Although chemical purification is very effective, by-products are not recoverable. Conversely, papain hydrolysis yields partially purified chitosan but permits aminoacids isolation, which is important in food industry. This method has other advantages such as low cost and easy accessibility of papain. Chitin and chitosan were characterized by thermogravimetric analysis, infrared spectrophotometry and capillary electrophoresis. Degree of N-acetylation (DA) was determined by cross-polarization magic angle spinning nuclear magnetic resonance (CPMAS 13CNMR) or potentiometry and crystallinity was measured by X ray diffraction.